2015
DOI: 10.1002/cncr.29288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lynch syndrome in a Middle Eastern population with colorectal cancer

Abstract: BACKGROUND: Lynch syndrome (LS; hereditary nonpolyposis colorectal cancer) is a common cause of hereditary colorectal cancer (CRC). CRC is the most common cancer diagnosed among males in Saudi Arabia but to the authors' knowledge there is a lack of data regarding the prevalence of LS in patients with CRC. There currently are no clear guidelines for the selection criteria for these patients to screen for LS. METHODS: A comprehensive molecular characterization was performed in a cohort of 807 CRC cases by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
(45 reference statements)
4
21
0
Order By: Relevance
“…This study demonstrated that the most commonly occurring deleterious germline mutation was that noted in MSH2 (56%, 5/9 cases), which was in agreement with other studies from the USA (8), Finland (33), Spain (11), Slovenia (34) and Saudi Arabia (35). The reason for the lower incidence of the MLH1 germline mutation (only one case) is unclear, despite the search for the possibility of germline MLH1 epimutations.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated that the most commonly occurring deleterious germline mutation was that noted in MSH2 (56%, 5/9 cases), which was in agreement with other studies from the USA (8), Finland (33), Spain (11), Slovenia (34) and Saudi Arabia (35). The reason for the lower incidence of the MLH1 germline mutation (only one case) is unclear, despite the search for the possibility of germline MLH1 epimutations.…”
Section: Discussionsupporting
confidence: 90%
“…In general, published detection rates have ranged an average of 2% to 3% for individuals with either CRC or EC, although there is some variation between different reports. 6,7,11,[15][16][17][18][19][20][21][22] Our detection rate may be lower for several reasons. Only one-half of all patients who were referred for genetic counseling ultimately attended a counseling session.…”
Section: Discussionmentioning
confidence: 95%
“…Most previous studies report a low incidence of hereditary CRC. Lynch syndrome, the most common hereditary malignancy, has an incidence of 1% and accounts for 2%–5% of all CRC cases,26,27 which is less than the cumulative incidence of multiple PMs. Hereditary CRC may be recognized as a typical representative group for multiple primary cancers.…”
Section: Discussionmentioning
confidence: 99%